2022
DOI: 10.3390/polym14235245
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of Morphology of Injection Molding Polypropylene Parts Induced by In-Mold Annealing

Abstract: It is generally recognized that high-temperature treatments, namely annealing, influence the microstructure and the morphology, which, in turn, determine the mechanical properties of polymeric parts. Therefore, annealing can be adopted to control the mechanical performance of the molded parts. This work aims to assess the effect of annealing on the morphology developed in isotactic polypropylene (iPP) injection-molded parts. In particular, a two-step annealing is adopted: the polymer is injected in a mold at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Morphology and mechanical performances depend on the crystallization experienced by molecules and the preserved orientation. Previous works demonstrated that crystallization occurs within higher temperature ranges when the mold temperature is high [31]; this would determine the increase in the crystalline degree and elastic modulus [34,35]. Crystallization and orientation depend on the temperature and shear rate experienced by the polymer chains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphology and mechanical performances depend on the crystallization experienced by molecules and the preserved orientation. Previous works demonstrated that crystallization occurs within higher temperature ranges when the mold temperature is high [31]; this would determine the increase in the crystalline degree and elastic modulus [34,35]. Crystallization and orientation depend on the temperature and shear rate experienced by the polymer chains.…”
Section: Discussionmentioning
confidence: 99%
“…Polymers 2024, 16, x FOR PEER REVIEW 15 of 18 that crystallization occurs within higher temperature ranges when the mold temperature is high [31]; this would determine the increase in the crystalline degree and elastic modulus [34,35]. Crystallization and orientation depend on the temperature and shear rate experienced by the polymer chains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the air leaks from the insert, the design of the insert and the mould is correct. If the air is trapped in a cavity, it prevents the melt from flowing [ 12 , 13 ].…”
Section: Flow Testmentioning
confidence: 99%